Comorbidity Burden and Functional Impairment in Chronic Heart Failure: Mapping the Link to NYHA Class in Outpatient Care - Ajeng Dwi Mega Sarie; Sinta Rahmah Sari (Integrative Perspectives of Social and Science Journal, 2026)
Background, heart failure places substantial burden on health systems worldwide, and its trajectory is shaped by cumulative comorbidity. Although the New York Heart Association classification remains a standard clinical tool, how it correlates with comorbidity burden in the Indonesian primary care setting has received limited empirical attention. This study examined the relationship between the age-adjusted Charlson Comorbidity Index and NYHA functional class among HF outpatients. Methods, this cross-sectional study was conducted at Klinik Pratama Paus Medika, Pekanbaru, Indonesia, from January to June 2025. Consecutive sampling identified 150 adult outpatients with chronic HF across all phenotypes. Comorbidity burden was quantified using the age-adjusted CCI; NYHA class I–IV was the primary outcome. Spearman's rank correlation, Kruskal-Wallis testing, and multivariable ordinal logistic regression—adjusted for age, sex, and HF etiology—were performed. Results, of 150 patients (mean age 63.1 ± 10.5 years; 54.7% male), most were in NYHA Class II (36.7%) or Class III (32.0%). Hypertension (74.7%), type 2 diabetes mellitus (42.0%), and chronic kidney disease (28.7%) yielded a median aCCI of 5 (IQR 4–7). Comorbidity burden showed a strong monotonic association with NYHA class (Spearman's ρ = 0.712; p < 0.001), and each one-point aCCI increase independently predicted higher NYHA class (aOR 1.95; 95% CI 1.67–2.28; p < 0.001), with the proportional odds assumption satisfied (p = 0.234). Conclusion, comorbidity burden, measured by the age-adjusted CCI, showed a strong, independent cross-sectional association with functional impairment severity in chronic HF. Incorporating multimorbidity profiling into HF care pathways may refine risk stratification and guide individualized, guideline-directed therapy.